The Association between Education Outside the Classroom and Physical Activity: Differences Attributable to the Type of Space? - Mads Bølling; Erik Mygind; Lærke Mygind; Peter Bentsen; Peter Elsborg (MDPI AG, 2021)
Education outside the classroom (EOtC) has become an attractive approach, not only for learning but also for health. This explorative, cross-sectional study investigated children's sedentary behaviours (SED), light physical activity (LPA) and moderate-to-vigorous PA (MVPA) on school days with an EOtC session in green space compared to school days with EOtC in other environments and without EOtC. Teachers from 17 Danish school classes practised EOtC for one school year on a weekly basis and self-reported the characteristics of the EOtC environment. The pupils' PA was device-measured for seven consecutive days in a random period during the school year with AX3 accelerometers. Across 617 pupils (age 9-13 years), PA intensity cases (N = 2264) on school days (8:10-14:00 h) with (n = 317) or without (n = 1947) EOtC were included in a mixed-effects regression analysis. Mean exposure to EOtC was 262 min per session. School days with green EOtC (e.g., parks, forests and nature schools) were associated with (mean, [95% CI]) −24.3 [−41.8, −7.7] min SED and +21.3 [7.7, 36.4] min LPA compared to school days with non-green EOtC (e.g., cultural and societal institutions or companies) and with +6.2 [−0.11, 11.48] min MVPA compared to school days with a school-ground EOtC. No sex differences were found. In conclusion, school days with green EOtC must be considered promising to counteract children's sedentary behaviours during school hours.